Effects of Pairing Correlations on Formation of Proton Halo in 9C - 韩瑞 李加兴 尧江明 姬娟霞 王建松 胡强 (Chinese physics letters, 2010)
Properties for the ground state of 9 C are studied in the relativistic continuum Hartree-Bogoliubov theory with the NLSH, NLLN and TM2 effective interactions. Pairing correlations are taken into account by a density-dependent δ-force with the pairing strength for protons determined by fitting either to the experimental binding energy or to the odd-even mass difference from the five-point formula. The effects of pairing correlations on the formation of proton halo in the ground state of 9C are examined. The halo structure is shown to be formed by the partially occupied valence proton levels p3/2 and p1/2.